Case study of early retirement intentions among police officers in Kedah contingent - Norulhaida, Mohd Rashid (2021)
The intention to retire early from employment has now become a concern for enforcement agencies, especially the Royal Malaysian Police (RMP), which often is put into the attention and focus of the community to obtain services because of its impact on the performance of the organization as a whole. Police officers are the most important source of human capital in ensuring that the role of the RMP organization functions at a high level of efficiency in facing challenging work environment situations. The focus of this study was to examine the organizational predictor factors to early retirement intentions among police officers serving in the Kedah Contingent. This study develops a conceptual framework to explain how independent variables such as workload, perceptions of the leader and career development can affect early retirement intentions i.e. dependent variables. The population of this study conducted on police officers working at the Kedah Contingent where the respondents consisted of police officers of various levels of positions covering (10) departments in the RMP team with different functions and duties. From the target population, a total of (278) police officers were distributed survey questionnaires for the purpose of data collection for analysis. The data obtained were analyzed using descriptive analysis and factual analysis. Descriptive analysis was conducted to obtain the response rate of the respondents' profile and organizational factors that influence the intention to retire early among police officers in the Kedah Contingent. For the hypotheses set out in the study, factual analysis was performed through correlation analysis to examine the relationship of early retirement intentions among police officers with predictor variables. Regression analysis was also performed to test the effect of the independent variable on the dependent variable. The results obtained assist in testing the effect of positive and meaningful relationships between the independent variables on the dependent variables. Overall, workload, perception of the leader and career development had a positive relationship to the intention of early retirement of police officers at the Kedah Contingent. The findings of this study can used by the RMP management to review human resource management related to the development of the work environment as well as the strengthening of relationships between employees.